Implementasi Pelaksanaan Administrasi Kesiswaan dalam Meningkatkan Mutu Pendidikan di MIN 4 Sukoharjo - Annafi' Nurul 'Ilmi Azizah; Natasya Alya Rahma; Mariska Ardiana (Ruang Publikasi Ilmiah, 2024)
This study examines the implementation of the student administration that exists at MIN 4 Sukoharjo. Student administration is a service provided by the school to the student participant. The student administration at MIN 4 Sukoharjo covers new student admission programmes, new student appointment, implementation of school order in an effort to improve student discipline, and the execution of competition participation from the school level to the international level. The research uses qualitative research methods with interviews, observations, and documentation data collection techniques. The subjects in this study are representatives of the head of the student department and teachers. The results of the study show that there is implementation of student administration from the admission of new students to the graduation of students. With the existence of student administration can help the course of the process of order that exists in the school, as well as support for the enforcement of related activities between teachers and students including the inclusion of a race to measure the level of students' ability inside and outside the school.